Evolocumab-induced delayed skin hypersensitivity reaction in a patient with familial hypercholesterolaemia - Porebski, Grzegorz; Dziadowiec, Alicja (Alergologia Polska - Polish Journal of Allergology, 2024)
In this report, we describe a patient with a delayed cutaneous hypersensitivity reaction to evolocumab, a human monoclonal antibody directed against the serine protease proprotein convertase subtilisin/kexin type 9 used to reduce low-density lipoprotein concentrations in the treatment of familial hypercholesterolaemia. The patient developed erythematous exfoliative lesions on the skin after the third administration of evolocumab. After each of the next three consecutive doses, the lesions worsened for 24 h, persisted for approximately 7 days, and then went into partial remission. Discontinuation of evolocumab resulted in a complete remission. Hypersensitivity reactions induced by biological drugs are becoming an increasing problem, but knowledge of these reactions is still limited. Our case report convincingly demonstrates the causal relationship between repeated drug exposure and the development and exacerbation of clinical symptoms. It also highlights a dilemma in the management of such clinical situations: the ‘treat-through’ strategy versus withdrawal of vital treatment.